Profiling mouse cochlear cell maturation using 10× Genomics single-cell transcriptomics - Xu, Zhenhang; Tu, Shu; Pass, Caroline; Zhang, Yan; Liu, Huizhan; Diers, Jack; Fu, Yusi; He, David Z. Z.; Zuo, Jian (Frontiers in Cellular Neuroscience, 2022)
Juvenile and mature mouse cochleae contain various low-abundant, vulnerable sensory epithelial cells embedded in the calcified temporal bone, making it challenging to profile the dynamic transcriptome changes of these cells during maturation at the single-cell level. Here we performed the 10x Genomics single-cell RNA sequencing (scRNA-seq) of mouse cochleae at postnatal days 14 (P14) and 28. We attained the transcriptomes of multiple cell types, including hair cells, supporting cells, spiral ganglia, stria fibrocytes, and immune cells. Our hair cell scRNA-seq datasets are consistent with published transcripts from bulk RNA-seq. We also mapped known deafness genes to corresponding cochlear cell types. Importantly, pseudotime trajectory analysis revealed that inner hair cell maturation peaks at P14 while outer hair cells continue development until P28. We further identified and confirmed a long non-coding RNA gene Miat to be expressed during maturation in cochlear hair cells and spiral ganglia neurons, and Pcp4 to be expressed during maturation in cochlear hair cells. Our transcriptomes of juvenile and mature mouse cochlear cells provide the sequel to those previously published at late embryonic and early postnatal ages and will be valuable resources to investigate cochlear maturation at the single-cell resolution.